Controlled Environment Specimen Transfer. (14th May 2014) - Damsgaard, Christian D.; Zandbergen, Henny; W. Hansen, Thomas; Chorkendorff, Ib; B. Wagner, Jakob
Abstract Specimen transfer under controlled environment conditions, such as temperature, pressure, and gas composition, is necessary to conduct successive complementary in situ characterization of materials sensitive to ambient conditions. The in situ transfer concept is introduced by linking an environmental transmission electron microscope to an in situ X-ray diffractometer through a dedicated transmission electron microscope specimen transfer holder, capable of sealing the specimen in a gaseous environment at elevated temperatures. Two catalyst material systems have been investigated; Cu/ZnO/Al2O3 catalyst for methanol synthesis and a Co/Al2O3 catalyst for Fischer–Tropsch synthesis. Both systems are sensitive to ambient atmosphere as they will oxidize after relatively short air exposure. The Cu/ZnO/Al2O3 catalyst, was reduced in the in situ X-ray diffractometer set-up, and subsequently, successfully transferred in a reactive environment to the environmental transmission electron microscope where further analysis on the local scale were conducted. The Co/Al2O3 catalyst was reduced in the environmental microscope and successfully kept reduced outside the microscope in a reactive environment. The in situ transfer holder facilitates complimentary in situ experiments of the same specimen without changing the specimen state during transfer.